Shape-controlled nanostructured MoO3/CeO2 catalysts for selective cyclohexene epoxidation - Sudarsanam, Putla; Singh, Nittan; Kalbande, Pavan Narayan (Catalysis Communications, 2022)
This study reported a vital role of CeO2 shape on the structure-activity properties of MoOx/CeO2 catalysts for cyclohexene epoxidation. Uniform dispersion of MoOx on the surface of shape-controlled CeO2 nanocubes (average particle size: 23.5 nm) and nanorods (average width: 6.3 nm and length: 15-95 nm) was found in MoOx/CeO2 nanomaterials. The MoOx/CeO2 nanocubes showed higher epoxide selectivity (97.3%) with 98.9% cyclohexene conversion, although it has lower BET surface area (30.2 m(2)/g) compared with MoOx/CeO2 nanorods (72.8 m(2)/g). The presence of more electropositive Mo6+ species and the strong Mo-Ce interaction led to improved catalytic efficacy of MoOx/CeO2 nanocubes in cyclohexene epoxidation.
Keywords: CeO2 nanocubes; CeO2 shapes; Nanosized MoOx/CeO2 catalyst; Selective epoxidation; Structure-activity properties